Allographs, Graphic Variants and Iconic Formulae in the Kohau Rongorongo Script of Rapa Nui (Easter Island) - Davletshin, Albert (Waka Kuaka, 2017)
In a writing system with a large number of signs, in particular in the case of a pictorial script, some similarity of two graphic designs is an insufficient basis for considering them to have the same reading value. This paper seeks to apply concepts developed in the graphic analysis of other pictorial writing systems to the still undeciphered script of Rapa Nui (Easter Island). The following technical terms are adapted and defined from both theoretical and practical points of view: sign, reading value, graphic design, allograph, graphic variant, seeming graphic variant, iconic formula, and complete, incomplete and false substitution. A modified version of the substitution method (method of inverse sign substitution) is proposed for verifying equivalences and differences between readings values corresponding to the graphic designs analysed in this paper. This method is based on the assumption that two graphic designs that possess the same reading value are in free distribution, so the probability of sign substitution between them should be close to the probability obtained by multiplying the probabilities of their occurrences in texts. Application of these technical concepts to the parallel texts discovered by Boris Kudrjavtzev shows that many graphically similar signs with different reading values have not been previously recognised. This conservative graphic analysis also has permitted the identification of "allographs" in the strict sense of the word, i.e., signs that look different but possess the same reading value. However, technically speaking, allograph in the strict sense of the word is an antonym for "graphic variant". It is suggested that the method of iconic formulae provides a useful foundation for future iconographic analysis of the highly pictorial signs of the Kohau Rongorongo script.